Counter-Memory and Power in Biographical Novels (The Baath Party and the Memory of Violence: A Study of "The World of Saddam Hussein" by Mahdi Haider) - Bian Abdul Sada, Researcher. Ahmed; Abdel Hussein Khalaf, Prof. Dr. Aqil (Basra studies journal, 2024)
The researcher adopts the concept of counter-memory, using its data as a study of private history and a critique of general authoritative history, to address a fundamental question: Has the biographical novel, starting from personal history, been able to critique and judge general history, exposing its authoritarian aspects and bias towards political power? This inquiry necessitated treating the novel as a counter-memory to the memory of authority. The study focuses on Mahdi Haider's novel "The World of Saddam Hussein," which highlights the flaws of that authority and rewrites the history of the Baath Party. It reveals the methods the party employed to seize power, centering around the character of Saddam Hussein, with other characters revolving around him.